2019
DOI: 10.1186/s13018-019-1406-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet-rich plasma on the degenerative rotator cuff tendinopathy according to the compositions

Abstract: BackgroundThere are controversies about platelet-rich plasma (PRP) as an established treatment option for rotator cuff (RC) tendinopathy. The purpose of the study was to find the relation of cellular component with clinical efficacy in RC tendinopathy and to find the composition of PRP in treating RC tendinopathy.MethodsA total 30 patients were recruited and divided into PRP and control groups. In the PRP group, 2 ml of PRP solution was injected to the hypoechoic lesion of degenerative supraspinatus via 22-gau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 59 publications
0
22
1
1
Order By: Relevance
“…[ 15 , 16 ] It contains several specific growth factors (such as vascular endothelial growth factor, epidermal growth factor, transforming growth factor-b, and insulin-like growth factor) that can stimulate healing, promote the inflammatory cascade, and accelerate tissue regeneration. [ 16 18 ] Recent study [ 19 ] reported that PRP injection play an effective and important role in the treatment of rotator cuff lesions, in cases where physiotherapy has been unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 , 16 ] It contains several specific growth factors (such as vascular endothelial growth factor, epidermal growth factor, transforming growth factor-b, and insulin-like growth factor) that can stimulate healing, promote the inflammatory cascade, and accelerate tissue regeneration. [ 16 18 ] Recent study [ 19 ] reported that PRP injection play an effective and important role in the treatment of rotator cuff lesions, in cases where physiotherapy has been unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, although analysis of the composition of PRP was performed, the concentrations of specific growth factors, such as interleukin-1b (IL-1b) and transforming growth factor-b1 (TGF-b1), were not analyzed. Kim et al 22 recently published a study in which cutoff values for these growth factors were presented to predict meaningful improvement in patients with degenerative rotator cuff tendinopathy. Although higher numbers of platelets and leukocytes are associated with an increase in growth factors, 37 analysis of concentrations of specific growth factors in addition to the concentration of platelets and leukocytes in PRP might give more insight in the optimal concentration of PRP for tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…43,48,51 In the nonoperative treatment of rotator cuff disease, such as partial-thickness rotator cuff tears and tendinopathy, conflicting results have been published about the efficacy of PRP. 3,[20][21][22]39,40,44,45,49 In comparison with corticosteroid injections, however, PRP seems to give superior results in the short term in patients with partial-thickness rotator cuff tears. 45,49 The use of PRP in the treatment of RCCT has never been investigated.…”
mentioning
confidence: 99%
“…PRP contains various growth factors and other bioactive molecules, which may regulate the aberrant inflammatory processes, regenerate tissue structures and thus promote tissue healing [ 15 ]. Autologous PRP involves a minimum risk of immune reactions and transmission of infectious diseases, and it has been widely used for the recovery of rotator cuff tendinopathy [ 16 ]. Previously, a RCT conducted by Lin et al [ 17 ] revealed that intra-articular injections of leukocyte-poor PRP can provide clinically significant functional improvement for at least 1 year in patients with mild-to-moderate osteoarthritis of the knee.…”
Section: Introductionmentioning
confidence: 99%